A lumped parameter vane pump model for system stability analysis. Issue 4 (2018) - Jenkins, Ryan P.; Ivantysynova, Monika
This paper presents a semi-empirical lumped parameter model developed for analysing the dynamic stability and performance limitations of a pressure compensated vane pump for an automotive application with low-cost components. The model calculates continuous displacement chamber pressure profiles and inertial effects for the determination of the internal forces acting on the vane pump's pivoting cam. Measurements conducted on a custom test stand were used to define a nonlinearly progressive bias spring model and a black box representation of the pump control system valves. Analysis of the complete model reveals that the performance limitations imposed by the control system valves, in terms of system stability and achievable controller bandwidth, are more restrictive than the limitations imposed by the low-cost vane pump and limit the that bandwidth to 1.84 Hz. The control system also imposes limitations to the system performance based on resonance phenomena which may be significant in some applications.